Wait a minute: The efficacy of discounting versus non-pecuniary payment steering - Angelika Welte (Bank of Canada, 2016)
Merchants who accept credit cards face payment processing fees. In most countries, the no-surcharge rule prohibits them from using surcharges to pass these fees on to customers. However, merchants are allowed to steer consumers toward less costly payment methods by offering discounts or using non-pecuniary incentives such as convenience and speed. Drawing upon micro data from a survey of Canadian households, I estimate a discrete choice model of consumers' payment methods to establish merchant costs for both of these strategies. I find that, while discounts are unprofitable because they subsidize a large portion of consumers who are already using cash and debit cards, non-pecuniary steering can be an effective strategy for transactions above 25.
Keywords: D12; E58; G28; 330; Bank notes; Market structure and pricing; Payment clearing and settlement systems